Wpływ rozszerzenia wschodniego na rynek pracy w UE - Kacperska, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The EU enlargement involving the Central and Eastern Europe states set a precedent, as never before in the history of European integration were so many states admitted. On May 1, 2004 the European Fifteen was joined by ten new states thus forming a group of 25 states. The objective of this paper is to present the desirable direction for Polish macroeconomic policy on the basis of the experience provided by integrationist processes, with particular emphasis on the experience of Ireland, Greece, Portugal and Spain. The main task of both the ‘old’ and the ‘new’ Union is to take advantage of the opportunities that result from this enlargement. Joint activities and policies should aim at the achievement of the EU strategic aim, established in Lisbon, i.e. at taking advantage of the technological change to achieve the maximum competitiveness and rapid growth pace of the EU economy so that appropriate conditions are created to provide full employment and increase the extent of regional cohesion in the EU.